Body dimensions of Nigerian cattle, sheep and goats - Hall, S.J.G. (Cambridge University Press, 1991)
A comparative study of body dimensions of indigenous cattle, sheep and goats. One hundred and thirty-six multiparous cows, 63 goats and 71 sheep were measured in breeding flocks and herds in Nigeria. The humped cattle breeds are large-bodied; humpless Kuri are narrow-bodied and tall in relation to their length when compared with British breeds. Their pelvic dimensions are small. The sheep and goats native to the coastal and middle belts (the West African Dwarf breeds) are miniature versions of those found in the north. Neither appeared to be achondroplasic but dwarfing had proceeded differently in the two species. The adult West African Dwarf goat is similar in its relative body proportions to the adult Northern goat, implying a proportional miniaturization. The West African Dwarf sheep appeared to be a neotenous form with body proportions similar to those of an immature sheep.